Analysis of Community Satisfaction with the Service Systems in Civil Registry Service Office, South Buru Regency using the TAM (Technology Acceptance Model) Method - Juneth Manuputty; Irwan Sembiring; Kristoko D Hartomo (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2023)
A good service system will satisfy the community, making that community’s contentment the deciding factor or the key factor in determining how successful an organization is in providing the service. This research aims to analyze the service system that has been available in the Department of Population and Civil Registration of Buru South district through the public satisfaction survey as well as to understand the services system that should be improved to minimize public dissatisfaction with the procedures provided by using the machine learning model, namely Random Forest Classifier technique to obtain a prediction of the satisfaction of the public with the services provided and perform validity testing on the prediction results obtained from the Random forest classifier technique using the Technology Acceptance Model. (TAM). The results of the trials carried out there are 3 determining factors to be able to increase public dissatisfaction namely the complaint service, the service process and the behavior of the officer supported by the validity test results using TAM with the results showing that the 3 services are valid means to be a factor that can be used to increase the public satisfaction with the result obtained from the T-computed value greater than T-table with the value for the Complaint Service 4.4794, service process 2.1345 and the Officer Behavior 1.9675 of the value of the table 1.6517.